Cytotoxic and anti-migratory effects of Ocimum gratissimum L. essential oil on prostate and cervical cancer cells in vitro - Laetitia Liz Coulibaly; Bagora Bayala; Julio Buñay; Aminata Marie Simone Amsalet Traoré; Pengdwendé Fabienne Ingrid Zongo; Marc Donald Wilfried Adico; Gilles Figueredo; Jean-Marc Lobaccaro; Jacques Simpore (Phytomedicine Plus)
Essential oil of Ocimum gratissimum L. (O. gratissimum) from Burkina Faso was evaluated for its antioxidant activity and for the first time, its cytotoxic properties, and effects on the cell cycle of LNCaP and HeLa cells, respectively derived from prostate and cervix tumors. Gas chromatography-flame ionization detection and gas chromatography-mass spectrometry identified 53 compounds, among them thymol (38.10 %) as the major component, which could explain the antiradical properties and cytotoxic activity of the essential oil on LNCaP and HeLa cells. The essential oil also exhibited antimigratory activity on the LNCaP cells with the reduction of their proliferation by inducing cell cycle arrest in the G0/G1 phase. While these results need to be confirmed in preclinical models, they support the potential use of cell cycle arrest of O. gratissimum essential oil as an antitumor agent, particularly in prostate cancer.